STRUCTURAL AND ELECTROCHEMICAL PROPERTIES OF REDUCED GRAPHENE OXIDE (RGO) SYNTHESISED USING AN IMPROVED MODIFIED HUMMERS METHOD AS ELECTRODE MATERIAL FOR ELECTRONICS APPLICATIONS (Nigerian Journal of Technology, 2019)
High quality reduced graphene oxide (RGO) nanosheets were prepared from natural graphite using an improved modified Hummers method. The morphological, structural and electrochemical properties of the RGO were characterised by scanning electron microscope (SEM), Raman spectroscopy, X-ray diffraction (XRD) analysis, Cyclic Voltammetry (CV) analysis and Electrochemical Impedance Spectroscopy (EIS) analysis. The SEM image of the RGO showed that, there was a small increase in the number of grain boundaries, indicating a collapse of the surface coalescence of the graphene oxide. The XRD peak at 24.56? corresponds to the (002) diffraction plane with the interlayer spacing along the c-axis of 2.0989 ?. The Raman shift for the reduced graphene oxide gives the ID/IG intensity ratio of 1.04. The RGO exhibited good electrochemical characteristics with energy density and power density of 19.2 Whkg-1 and 149.3 Wkg-1 respectively.  http://dx.doi.org/10.4314/njt.v38i4.24